The impact of foreign direct investment on economic growth in Egypt during the period 1980-2020 - اسماعيل رولا (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Given the importance of foreign direct investment in financing the economic development process, especially for developing countries, and its importance in raising economic growth rates in the country, the aim of this research is to study foreign direct investment and its relationship to the economic growth of the Egyptian economy during the period from 1980 to 2020. The research consists of two main parts: the first part includes a study of the development of foreign direct investment in Egypt during the studied period, while the second part includes an econometric study to find out the impact of this investment on the rate of economic growth in Egypt during this period. The research concludes that there is a positive relationship between foreign direct investment and economic growth in Egypt, as an increase in foreign direct investment as a percentage of GDP leads to an increase in the rate of economic growth. Foreign investments lead to a number of positive effects that contribute to raising growth rates, such as increasing job opportunities, reducing unemployment rates, increasing exports, and increasing the country’s ability to compete abroad.